Employment, hours of work and the optimal design of earned income tax credits - Richard Blundell; Andrew Shephard (Institute for Fiscal Studies (IFS), 2008)
This paper examines the tax schedule for low income families with children. We take an optimal tax approach based on a structural labour supply model which incorporates unobserved heterogeneity, fixed costs of work, childcare costs and the detailed non-convexities of the tax and transfer system. The motivation is the British earned income tax credit reform (WFTC) and its interaction with the tax and transfer system for lone parents. Our analysis also examines the case for the use of hours-contingent payments. The results point to a tax schedule which depends on the age of children, with tax credits only optimal for low earners with school age children. The results also suggest a welfare improving role for hours-contingent payments although this is mitigated when hours cannot be monitored or recorded accurately by the tax authorities.
Keywords: 330; Einkommensteuer; Optimale Besteuerung; Steuerbegünstigung; Arbeitsangebot; Theorie; Großbritannien